STUDY OF THE MORPHOLOGY AND THERMOSTABILITY OF POLYAMPHOLYTE PRODUCED ON THE BASIS OF AMINOACETIC ACID IMMOBILIZATION IN EPOXY MATRIX - Umirova Gulnora Abdurakhmonovna; Turaev Khayit Khudainazarovich; Djalilov Abdulakhat Turapovich; Kasimov Sherzod Abduzairovich (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of this study is the synthesis and study of a covalently immobilized chelate-forming ligand for the extraction of non-ferrous and noble metal ions. To achieve this goal, a nitrogen-containing immobilized ligand based on aminoacetic acid, epoxy resin, and polyethylene polyamine was synthesized and studied. The article studies the thermal stability and surface morphology of an immobilized ligand obtained on the basis of covalent fixation of aminoacetic acid on an epoxy matrix. As a result of thermal studies, it was found that the resulting ligand is stable up to 195°C. The microscopic structure and elemental analysis of the ligand and its coordination compound with Cu2+ ions were studied using a scanning electron microscope. The microstructure of the surface of the obtained ligand was measured at the level of 100 μm; it was found that it is porous and has high sorption properties.